empowering diary in recount text for student's writing skills: recount text - Kusuma jaya, Dwi jayati (LP3MKIL, 2022)
The objectives of this research is to describe the process of teaching writing recount texts by using diary, to find out the teacher’s problem sand students’ responses toward using diary. The research employs a descriptive qualitative research. Findings show the use of diary in teaching writing recount text could help and develop students’ writing. The teacher explained and instructed in procedural teaching practice to diary usage. However, the problems were limited time at the activities and lack of the teacher’s knowledge. Generally, the use of diary gave a creativity both the teacher and students and made students motivated in learning writing. Thus, diary is one of effective ways to express the students’ ideas in writing because they can tell prior activities or experiences happened.